Membangun Heritage dalam Penerapan Transformasi Digital Museum Kekhatuan Semaka Pekon Sanggih Unggak Kecamatan Bandar Negeri Semuong Kabupaten Tanggamus - Rangga Firdaus; Wayan Suana; Afif Rahman Riyanda; Margaretha Karolina Sagala (Jurnal Informatika Global, 2022)
Museums are a place for the community to recognize and understand existing cultural and historical values. However, inadequate and inadequate facilites affect public interest in visiting museums, including the Semaka Kekhatuan Museum in Pekon Sanggih Unggak, Bandar Negeri Semuong. District, Tanggamus Regency. Therefore, this study aims to make a video documentation of the collection of historical objects in the Semaka Kekhatuan Museum and develop a web-based system for developing a video documentation system for the collection oh historical objects at the Semaka Kekhatuan Museum, Pekon Sanggih Unggak, Bandar Negeri Semuong District, Tanggamus Regency. This study uses a type of research and development method (Research and Development). This study uses the ADDIE model which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data in this development research were collected using to data collection methods, namely the interview method and the questionnaire method. The data generated are in the form of questionnaires resulting from interviews, questionnaires resulting from needs analysis, questionnaires on the results of material and design expert tests, and questionnaires on the results of attractiveness and convenience tests. This can be seen on a website that contains a video documenting the collection of historical object of the Semaka Kekhatuan Museum in the form of the Kekhatuan Semaka Museum, Pekon Sanggih Unggak, Bandar Negeri Semuong District. Tanggamus Regency.Keywords: Collection of Historical Objects, Kekhatuan Semaka Museum, Video Documentation